Ionic Polymer Metal Composites for Sensors and Actuators - Inamuddin; Asiri, Abdullah M. (Engineering Materials,, 2019)
This book discusses the fundamental of bending actuation with a focus on ionic metal composites. It describes the applications of ionic polymer metal composite (IPMC) actuators, from conventional robotic systems to compliant micro robotic systems used to handle the miniature and fragile components during robotic micro assembly. It also presents mathematical modelings of actuators for engineering, biomedical, medical and environmental systems. The fundamental relation of IPMC actuators to the biomimetic systems are also included.